2014
DOI: 10.1111/tmi.12291
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and pulse oximetry in childhood pneumonia: surveys of clinicians and student clinicians in Cambodia

Abstract: Abstractobjective To better understand the availability of oxygen and pulse oximetry, barriers to use, clinician perceptions and practices regarding their role in the management of childhood pneumonia, and the formal education and training regarding these technologies received by student clinicians in Cambodia. results Common barriers to use included a lack of policies and guidelines, as well as a lack of training. In the student clinician survey, 332 graduating medical and nursing students were surveyed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Our findings are from paediatric areas within medium-sized Nigerian hospitals and may be less relevant outside this context. However, poor oximetry practices are common in hospitals throughout the world, particularly in low-income and middle-income countries,12–16 and our realist evaluation approach enables many lessons to be shared. Our study looked specifically at oximetry; however, our findings may be relevant to the introduction of other care practices, particularly those that involve the introduction of new health technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are from paediatric areas within medium-sized Nigerian hospitals and may be less relevant outside this context. However, poor oximetry practices are common in hospitals throughout the world, particularly in low-income and middle-income countries,12–16 and our realist evaluation approach enables many lessons to be shared. Our study looked specifically at oximetry; however, our findings may be relevant to the introduction of other care practices, particularly those that involve the introduction of new health technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility studies have shown that nurses and community health workers are able to use pulse oximeters effectively 10 11. However actual use of oximetry remains low—even when pulse oximeters are available 12–16. Experience from previous oximetry implementation projects suggests that while oximetry itself is not complicated, integrating oximetry into routine care practices is complex,17–19 requiring substantial behaviour change, and being influenced by a range of individual, social and environmental influences 20…”
Section: Introductionmentioning
confidence: 99%
“…Pulse oximetry, the ‘fifth pediatric vital sign’ [ 19 ] supplemented by treatment with oxygen was found to be a feasible and cost effective intervention for childhood pneumonia with 35% reduction in mortality in Papua New Guinea [ 20 ]. Unfortunately even though pulse oximeters and oxygen are available, they are underutilized by health workers in developing countries [ 21 , 22 ]. Pulse oximetry to document hypoxia in community acquired pneumonia is not only endorsed by professional societies in developed countries [ 23 , 24 ] but also stated in recent WHO guidelines[ 6 ] and our findings support these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, evidence on the uptake of pulse oximetry in LMIC is limited. Available estimates suggests it remains low, ranging from less than 30% to more than 70% across different LMIC settings . There are examples of pulse oximeter implementation being feasible in LMIC settings, including Malawi and Nigeria, and resulting in improved referral decision‐making .…”
Section: Introductionmentioning
confidence: 99%